Peran Pendidikan Karakter Terhadap Perkembangan Anak Usia Dini - Suharwanto (STIT Muslim Asia Afrika, 2019)
This paper contains the Role of Character Education on Early Childhood Development in Kindergarten Islam Perkasa Cinangka – Sawangan Depok. This paper focuses on Early Childhood development. This study used a qualitative descriptive approach. The subjects in this study were principals, teachers and students at TK Islam Perkasa sawangan Depok city. Data were collected through observation, interview, and documentation methods. The collected data is analyzed using an interactive analysis model. The research data were tested again using extended participation, observation diligence and trianggulation. The result of this study is the application of character education in Kindergarten Islam Perkasa carried out through the process of: a) planning by including the theme of learning character values into the content of the school curriculum, RPPH and RPPM. b) implementation of learning that includes learning activities, programmed activities, routine activities, habituation, spontaneity and example, and c) assessment using observation, anecdotal records, potopolio and periodic assessments.